Non-alcoholic Wernicke’s Encephalopathy mimicking neuromyelitis optica spectrum disorder in a young woman: a case report and literature review - Zilioli, Alessandro; Misirocchi, Francesco; Mutti, Carlotta; Romano, Sonia; Minetti, Matteo; Chierici, Elisabetta; Florindo, Irene; Spallazzi, Marco; Zinno, Lucia (Acta Biomedica Atenei Parmensis, 2023)
Wernicke’s encephalopathy is an under-recognized life-threatening disease caused by thiamine (vitamin B1) deficiency. It has historically been related to chronic alcoholic intake but other causes of malnutrition, such as invasive gastric surgery and hyperemesis, have been linked to the onset of this illness over the years, often presenting with atypical clinical manifestations. Herein we report a case of a young obese woman affected by non-alcoholic Wernicke’s Encephalopathy following a minimally invasive gastrointestinal surgery. She showed an unusual clinical profile characterized by prominent subacute neuro-ophthalmological involvement which combined to her juvenile age, overweight condition and brain lesions, have made diagnosis challenging due to similarities with Neuromyelitis Optica Spectrum Disorder. Our case underscores the relevance of prompt diagnosis in order to prevent the development of irreversible neuropathological changes and to avoid the use of a long-term immunosuppressive treatment.